2017
DOI: 10.1007/s11103-017-0637-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, classification, evolutionary analysis and gene expression patterns of the protein kinase gene family in wheat and Aegilops tauschii

Abstract: In this study we systematically identified and classified PKs in Triticum aestivum, Triticum urartu and Aegilops tauschii. Domain distribution and exon-intron structure analyses of PKs were performed, and we found conserved exon-intron structures within the exon phases in the kinase domain. Collinearity events were determined, and we identified various T. aestivum PKs from polyploidizations and tandem duplication events. Global expression pattern analysis of T. aestivum PKs revealed that some PKs might partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 74 publications
11
28
0
Order By: Relevance
“…The group containing the most kinases is the RLK-Pelle group (Gish and Clark, 2011) and, similar to findings in other kinomes (Singh et al, 2014;Wei et al, 2014;Zulawski et al, 2014;Liu et al, 2015;Yan et al, 2017Yan et al, , 2018Zhu et al, 2018a, b), we found that the RLK-Pelle group had the most members in our study. This expansion in the Sbi and Ssp kinomes is apparently related to a few specific families within this group, most notably the LRR, RLCK, DLSV, L-LEC and SD-2b families.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The group containing the most kinases is the RLK-Pelle group (Gish and Clark, 2011) and, similar to findings in other kinomes (Singh et al, 2014;Wei et al, 2014;Zulawski et al, 2014;Liu et al, 2015;Yan et al, 2017Yan et al, , 2018Zhu et al, 2018a, b), we found that the RLK-Pelle group had the most members in our study. This expansion in the Sbi and Ssp kinomes is apparently related to a few specific families within this group, most notably the LRR, RLCK, DLSV, L-LEC and SD-2b families.…”
Section: Discussionsupporting
confidence: 92%
“…In Sbi, PK genes were more commonly located in subtelomeric regions. This pattern was even more evident when only tandemly duplicated PKs were considered; similar (though less pronounced) patterns were observed in the kinomes of soybean (Liu et al, 2015), T. aestivum (Yan et al, 2017), Gossypium raimondii and Gossypium barbadense (Yan et al, 2018). Yan et al (2017) noted that this pattern is consistent with T. aestivum's higher gene and expressed sequence tag (EST) densities in distal regions of chromosomes and inferred that this location pattern of PKs could indicate chromosomal rearrangements.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations